UKRAINIAN ETHNOPEDAGOGY AS A FACTOR OF ENRICHMENT EDUCATIONAL IMPACT ON THE INDIVIDUAL - S.B. Furduy (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the question of Ukrainian ethnopedagogics as a factor o f educational influence over personality.